Pension Reform, Investment Restrictions and Capital Markets - Roldos, Jorge (IMF Policy Discussion Papers; Policy Discussion Paper ;, 2004)
Pension reform in several emerging market countries has been associated with rapid growth in assets under management and a positive impact on the development of local securities markets. However, limitations on such development may lead to asset price distortions, bubbles, and concentration of risks. Regulatory limits on pension fund investments are assessed in light of these risks and developments in modern portfolio theory. A gradual but decisive loosening of restrictions on equity and foreign investments is recommended. Changes in these regulations ought to be coordinated with measures designed to foster the development of local securities markets as well as with macroeconomic policies.